Information Technology is Now Used Everywhere - Rajaboev Shahboz Shodiyevich; Raxmatov Ozodbek Aktam O'g'li (Miasto Przyszłości, 2024)
: Conducting teleconsultations for patients and employees, sharing information about patients between different institutions, remote recording of physiological indicators, monitoring operations in real time - all this is provided by the introduction of information technologies into medicine. This brings healthcare information to a new stage of development, positively affecting all aspects of its activity. The introduction of IT in the healthcare sector allows to increase the quality of service, significantly speed up the work of employees and reduce the costs of providing services to patients.